Engineering of antimicrobial peptide Brevinin-1pl: arginine, lysine, and histidine substitutions enhance antimicrobial-anticancer efficacy with reduced cytotoxicity - Wang, Jingkai; Zeng, Fanli; Chen, Xiaoling; Wang, Tao; Wang, Lei; Zhou, Mei; Jiang, Yangyang; Chen, Tianbao; Fang, Yongfei; Zhang, Jinwei (Frontiers in Chemistry, 2025)
IntroductionAntimicrobial peptides (AMPs) are promising candidates for combating multidrug-resistant infections, but their clinical application is often limited by challenges such as poor selectivity and high cytotoxicity. This study aimed to optimize the therapeutic potential of brevinin-1pl, a frog-derived AMP with broad-spectrum antimicrobial and anticancer activities.MethodsMajor experimental approaches encompassed antibacterial activity evaluation, hemolytic potential assessment, bactericidal rate determination via time-kill kinetics, SYTOX Green-based membrane integrity analysis, and MTT assays for anti-proliferative effects.ResultsSubstitutions with arginine (brevinin-1pl-2R and brevinin-1pl-5R) enhanced activity against Gram-positive bacteria but reduced efficacy against Gram-negative strains. Lysine substitution (brevinin-1pl-6K) decreased activity against Gram-positive bacteria due to reduced hydrophobicity. In contrast, histidine substitution (brevinin-1pl-3H) showed diminished activity against Gram-negative bacteria (e.g., MRSA MIC increased from 2 µM to 4 µM) but reduced hemolysis, indicating improved selectivity. Mechanistic studies using SYTOX green assays confirmed membrane disruption as a primary mode of action, while suggesting alternative mechanisms for Gram-positive Enterococcus faecium and Gram-negative Escherichia coli. The brevinin-1pl and its analogues demonstrated significant inhibitory efficacy against both MCF-7 breast cancer cells and H838 non-small cell lung cancer cells at a concentration of 10–4 M. Notably, brevinin-1pl-3H exhibited low cytotoxicity toward normal HaCaT cells despite its high hydrophobicity, suggesting potential for dermatological applications.ConclusionThese findings demonstrate that strategic amino acid substitutions can optimize the therapeutic potential of AMPs, offering a promising approach to develop peptides with enhanced efficacy and reduced clinical side effects.